World language teacher education : transitions and challenges in the twenty-first century - Davis, Jacqueline F. (Contemporary language education (Greenwich, Conn.), 2010)
The significant change in public schools over the last two decades warrants a response in how we prepare teachers. This volume is an effort to share the contributors' knowledge, experience and ideas with colleagues, particularly with novice language teacher educators. The suggestions in the chapters are primarily provided for the teaching methods course, but many can be adapted to other education courses or for professional development programs. The first section of the introduction provides a review of issues identified in teacher education including debates, accountability, and government influence over education. The second section explores teacher educators in the literature such as issues in their practice, and a focus on foreign language teacher educator practice. The third section provides a brief overview of the chapters in the book.